Structural consequences of weak interactions in dispirooxindole derivatives. Issue 11 (1st November 2015) - Ravikumar, Krishnan; Sridhar, Balasubramanian; Nanubolu, Jagadeesh Babu; Karthik, Govindaraju; Reddy, Basi Venkata Subba
Abstract : Spiro scaffolds are being increasingly utilized in drug discovery due to their inherent three‐dimensionality and structural variations, resulting in new synthetic routes to introduce spiro building blocks into more pharmaceutically active molecules. Multicomponent cascade reactions, involving the in situ generation of carbonyl ylides from α‐diazocarbonyl compounds and aldehydes, and 1, 3‐dipolar cycloadditon with 3‐arylideneoxindoles gave a novel class of dispirooxindole derivatives, namely 1, 1′′‐dibenzyl‐5′‐(4‐chlorophenyl)‐4′‐phenyl‐4′, 5′‐dihydrodispiro[indoline‐3, 2′‐furan‐3′, 3′′‐indoline]‐2, 2′′‐dione, C44 H33 ClN2 O3, (I), 1′′‐acetyl‐1‐benzyl‐5′‐(4‐chlorophenyl)‐4′‐phenyl‐4′, 5′‐dihydrodispiro[indoline‐3, 2′‐furan‐3′, 3′′‐indoline]‐2, 2′′‐dione, C39 H29 ClN2 O4, (II), 1′′‐acetyl‐1‐benzyl‐4′, 5′‐diphenyl‐4′, 5′‐dihydrodispiro[indoline‐3, 2′‐furan‐3′, 3′′‐indoline]‐2, 2′′‐dione, C39 H30 N2 O4, (III), and 1′′‐acetyl‐1‐benzyl‐4′, 5′‐diphenyl‐4′, 5′‐dihydrodispiro[indoline‐3, 2′‐furan‐3′, 3′′‐indoline]‐2, 2′′‐dione acetonitrile hemisolvate, C39 H30 N2 O4 ·0.5C2 H3 N, (IV). All four compounds exist as racemic mixtures of the SSSR and RRRS stereoisomers. In these structures, the two H atoms of the dihydrofuran ring and the two substituted oxindole rings are in a trans orientation, facilitating intramolecular C—H...O and π–π interactions. These weak interactions play a prominent role in the structural stability and aid the highly regio‐ and diastereoselective synthesis. In each of the four structures, the molecular assembly in the crystal is also governed by weak noncovalent interactions. Compound (IV) is the solvated analogue of (III) and the two compounds show similar structural features.